Analysis of the Bearing Capacity of Bore Pile Foundation on the C83 Suites Building Countruction Project in Cirebon - Zuliyanto, Muhammad Dwi; Budirahardjo, Slamet; Rizani, Mohammad Debby (Science and Technology Research Centre, Universitas PGRI Semarang, 2025)
In soil testing using sondir in the C83 Suites building construction project in Cirebon City, the lowest soil carrying capacity was found at the S-1 point. In this study, an analysis of the carrying capacity of a bore pile with a diameter of 40 centimeters with a depth of 12 meters was carried out to obtain a comparison of calculation results using three methods, namely the LCPC (Bustamante Gianeselli) method, the Schmertmann Nottingham method, and the Direct method. The results of the calculation using the LCPC method (Bustamante Gianselli) obtained Qu= 232,001 tons, Qa = 92,800 tons. Then using the Schmertmann Nottingham method, Qu= 301,764 tons was obtained, Qa = 120,705 tons. Meanwhile, using the Direct method, it was obtained at the S-1 point with Qu= 115,158 tons, Qa = 46,063 tons.